Risk for Infantile Spasms after Acute Symptomatic Neonatal Seizures - Glass, Hannah C. (Epilepsia, 2020)
OBJECTIVE: Infantile spasms (IS) is a severe epilepsy in early childhood. Early treatment of IS provides the best chance of seizure remission and favorable developmental outcome. We aimed to develop a prediction rule to accurately predict which neonates with acute symptomatic seizures will develop IS. METHODS: We used data from the Neonatal Seizure Registry, a prospective, multicenter cohort of infants with acute symptomatic neonatal seizures born 7/2015-3/2018. Neonates with acute symptomatic seizures who received clinical EEG and MRI and were <2 years at the time of enrollment were included. We evaluated the association of neonatal EEG, MRI, and clinical factors with subsequent IS using bivariate analysis and best subsets logistic regression. We selected a final model through a consensus process that balanced statistical significance with clinical relevance. RESULTS: IS developed in 12 of 204 infants (6%). Multiple potential predictors were associated with IS, including Apgar scores, EEG features, seizure characteristics, MRI abnormalities, and clinical status at hospital discharge. The final model included three risk factors: (1) severely abnormal EEG or ≥3 days with seizures recorded on EEG, (2) deep gray or brainstem injury on MRI, and (3) abnormal tone on discharge exam. The stratified risk of IS was: no factors 0% (0/82, 95% confidence interval 0-4%), one or two factors 4% (4/108, 95% CI 1-9%), and all three factors 57% (8/14, 95% CI 29-83%). SIGNIFICANCE: IS risk after acute symptomatic neonatal seizures can be stratified using commonly available clinical data. No child without risk factors, versus >50% of those with all three factors, developed IS. This risk prediction rule may be valuable for clinical counseling as well as for selecting participants for clinical trials to prevent post-neonatal epilepsy. This tailored approach may lead to earlier diagnosis and treatment and improve outcomes for a devastating early-life epilepsy.